Entre a cultura da honra e o crime: representações femininas no Diário de Pernambuco (1850-1889). - Costa, Daniela Cavalcanti Bruto da (2021)
Problematization plays an important role in History classes. It is true that it has its origins in the concerns about the present and, in times of persecution of the human sciences, of questioning scientific thoughts and the unceasing anti-feminist and racist discourses and practices, this simple question takes on even greater relevance. In this sense, the present work proposes to problematize the female representations in the Diario de Pernambuco between 1850 and 1889, a newspaper of great circulation and political importance in those years, within the period of the construction of Brazil as a nation. The analysis focused on news of crimes involving women, as perpetrators or victims, aimed at noticing this female presence and, in particular, the interpretations of their actions. The methodology followed the qualitative and sampling method as a criterion, with 195 news items being selected and cataloged, meeting the criteria defined for the analysis of detailed information about the people involved and about the crime. Using as a parameter the guidelines proposed by the BNCC for secondary education, when young people are expected to elaborate hypotheses and arguments based on reliable sources and exercise systematic doubt, 15 news items were selected for the elaboration of a board game. The game was designed to be used by sophomore high-school students at Colégio Grande Passo, a private school in the south of Recife whose public is mostly composed of middle-class students, and that proposes a humanitarian development, providing relative autonomy to the application of pedagogical practices proposed by the BNCC. At this stage, when young people already have greater cognitive capacity and ability to articulate information and knowledge, discussions about gender identity are more present, adapting the History content to the research period, providing the students with an important scientific and cultural repertoire. Thus, through an experience within an interdisciplinary project, there was the exercise of contact with historical sources, interaction among students, the elaboration of hypotheses and, most important, an analysis of female representations as part of a discursive construction in the nineteenth century.